ANDROID BASED BODY MASS INDEX DETECTION - Mutia Utami; Muhammad Nasir; Mursyidah (PT. Radja Intercontinental Publishing, 2024)
Obesity and malnutrition are important health problems. To deal with the big risk of health problems, early detection can be carried out by using a standard Body Mass Index (BMI) formula. This detection application will take a photo of the object, which will later determine its Body Mass Index. The image obtained was RoIed using the Thersholding technique with a single threshold value of 160. It is hoped that it can help someone find out the value and category of their Body Mass Index by processing digital images via pixels. The research data obtained is able to inform body weight and pixel height from digital images so that the application can detect Body Mass Index efficiently and practically and can be used by the wider community with a Body Mass Index Detection accuracy of 70% at a distance of 230 cm between the camera and the object.